2018
DOI: 10.1021/acsnano.8b02188
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabright Polymer-Dot Transducer Enabled Wireless Glucose Monitoring via a Smartphone

Abstract: Optical methods such as absorptiometry, fluorescence, and surface plasmon resonance have long been explored for sensing glucose. However, these schemes have not had the clinical success of electrochemical methods for point-of-care testing because of the limited performance of optical sensors and the bulky instruments they require. Here, we show that an ultrasensitive optical transducer can be used for wireless glucose monitoring via a smartphone. The optical transducer combines oxygen-sensitive polymer dots (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 44 publications
0
88
0
Order By: Relevance
“…[ 7 ] With multicolor emissions that span the entirety of the visible spectrum and extend to the near‐infrared window, Pdots have been used extensively in cellular imaging, optical sensing, in vivo fluorescence imaging, photoacoustic imaging, and phototherapy. [ 8 ] Owing to their high fluorescence brightness, fast radiation rates, and good stability, Pdots have also been deployed in super‐resolution nanoscopy. [ 9 ] Combining versatile polymer chemistry with superior optical properties, Pdots provide promising strategies for the design of new fluorophores that can overcome the labeling bottleneck in ExM.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] With multicolor emissions that span the entirety of the visible spectrum and extend to the near‐infrared window, Pdots have been used extensively in cellular imaging, optical sensing, in vivo fluorescence imaging, photoacoustic imaging, and phototherapy. [ 8 ] Owing to their high fluorescence brightness, fast radiation rates, and good stability, Pdots have also been deployed in super‐resolution nanoscopy. [ 9 ] Combining versatile polymer chemistry with superior optical properties, Pdots provide promising strategies for the design of new fluorophores that can overcome the labeling bottleneck in ExM.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging techniques are not popular in this category, as the adapter consists of special electronics that are designed specifically to target a unique chemical compound . Using a smartphone proved to be cost effective (see Figure 12), and extremely accurate results were reported when comparing the performance of the smartphone‐based adapters to those of laboratory equipment and devices with a low CV%, a high regression coefficient, lower costs, and a low LOD (see Figures to ) . Zhao et al, as shown in Figure A, developed a fluorescent smartphone‐based label‐free sensor to detect Fe (III) by employing the quenching effect.…”
Section: Resultsmentioning
confidence: 99%
“…[168][169][170][171][172][173][174] Using a smartphone proved to be cost effective (see Figure 12), and extremely accurate results were reported when comparing the performance of the smartphone-based adapters to those of laboratory equipment and devices with a low CV%, a high regression coefficient, lower costs, and a low LOD (see Figures 10 to 13). [175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192] Zhao et al, 193 as shown in Figure 8A, developed a fluorescent smartphone-based label-free sensor to detect Fe (III) by employing the quenching effect. The 3D printed adapter uses a 365-nm UV LED and a smartphone camera.…”
Section: Electrochemical Applicationsmentioning
confidence: 99%
“…[65] In the presence of glucose, efficient FRET from Pdot 11 to PdTFPP resulted in increased emission at 672 nm (Figure 5a) This Pdot-based probe could selectively distinguish hyperglycemia from euglycemia in vivo, and the intensity ratio of phosphorescence (I 672 /I 425 ) of Pdots could be used to quantitatively determine the concentrations of glucose. Wu's group designed a Pdot-based optical transducer consisting of Pdot 11 (poly [9,9-dihexylfluorenyl-2,7-diyl], PDHF) doped with palladium(II) meso-tetra (pentafluorophenyl) porphine (PdTFPP) to form the oxygen-sensitive Pdots, accompanied by the surface conjugation of glucose oxidase (GOx) to detect and monitor glucose levels continuously via a smartphone.…”
Section: Glucose Monitoringmentioning
confidence: 96%
“…Reproduced with permission [65]. True-color photographs of mice and the corresponding magnified regions at different blood glucose levels.…”
mentioning
confidence: 99%